Blood Neurofilament Light in Progressive Multiple Sclerosis: Post Hoc Analysis of 2 Randomized Controlled Trials. (24th May 2022) - Leppert, David; Kropshofer, Harald; Häring, Dieter A.; Dahlke, Frank; Patil, Ashwini; Meinert, Rolf; Tomic, Davorka; Kappos, Ludwig; Kuhle, Jens
Abstract : Background and Objectives: To investigate the potential of plasma neurofilament light (pNfL) as a biomarker of disease progression and treatment response in progressive multiple sclerosis (PMS) with and without acute disease activity. Methods: A post hoc blinded analysis of pNfL levels in 2 placebo-controlled, phase 3 studies in secondary progressive multiple sclerosis (SPMS; EXPAND) and primary progressive multiple sclerosis (PPMS; INFORMS) using siponimod and fingolimod, respectively, as active compounds was performed. pNfL levels were quantified using a single molecule array (Homebrew Simoa) immunoassay from stored ethylenediaminetetraacetic acid (EDTA) plasma samples of all patients who consented for exploratory biomarker analysis in either study; pNfL levels were divided into high (≥30 pg/mL) and low (<30 pg/mL) at baseline. We investigated the association of pNfL levels with disability progression, cognitive decline, and brain atrophy and their sensitivity to indicate treatment response through clinical measures. Results: We analyzed pNfL in 4, 185 samples from 1, 452 patients with SPMS and 1, 172 samples from 378 patients with PPMS. Baseline pNfL levels were higher in SPMS (geomean 32.1 pg/mL) than in PPMS (22.0 pg/mL; p < 0.0001). In both studies, higher baseline pNfL levels were associated with older age, higher Expanded Disability Status Scale score, more Gd + lesions, and higher T2 lesion load (all p < 0.05). Independent of treatment, high vs low baseline pNfL levels were associated with significantly higher risks of confirmed 3-month (SPMS [32%], hazard ratio [95% CI] 1.32 [1.09–1.61]; PPMS [49%], 1.49 [1.05–2.12]) and 6-month disability progression (SPMS [26%], 1.26 [1.01–1.57]; PPMS [48%], 1.48 [1.01–2.17]), earlier wheelchair dependence (SPMS [50%], 1.50 [0.96–2.34]; PPMS [197%], 2.97 [1.44–6.10]), cognitive decline (SPMS [41%], 1.41 [1.09–1.84]), and higher rates of brain atrophy (mean change at month 24: SPMS, −0.92; PPMS, −1.39). Baseline pNfL levels were associated with future disability progression and the degree of brain atrophy regardless of presence or absence of acute disease activity (gadolinium-enhancing lesions or recent occurrence of relapses before baseline). pNfL levels were lower in patients treated with siponimod or fingolimod vs placebo-treated patients and higher in those having experienced disability progression. Discussion: pNfL was associated with future clinical and radiologic disability progression features at the group level. pNfL was reduced by treatment and may be a meaningful outcome measure in PMS studies. Trial Registration Information: EXPAND (ClinicalTrials.gov identifier: NCT01665144) and INFORMS (ClinicalTrials.gov identifier: NCT00731692).